THE DECONSTRUCTION OF NAHDLATUL ULAMA ACTIVISTS AGAINST THE CONCEPT OF AGRARIAN REFORM BASED ON FIQH OF PRIORITIES - Herlindah Herlindah; Siti Rohmah; In'amul Mushoffa; Abdul Kodir (Jurisdictie: Jurnal Hukum dan Syariah, 2023)
After several years of suspension, agrarian reform was re-implemented as a way to achieve agrarian justice. This policy was stipulated in the Presidential Regulation Number 86 of 2018 concerning the Implementation of Agrarian Reform which is framed in the Agrarian Reform and Social Forestry (RAPS). However, many groups, mainly the Nahdlatul Ulama (NU) with their strong activism in the agrarian struggle, deeply criticized this policy. This research will examine how NU activists deconstruct the concept of agrarian reform in the RAPS policy using the priority fiqh theory. Fiqh of priorities was initiated to consider the implementation of charity acts or policies deserving the priority of concern based on Shariah principles. This study applied empirical and normative legal research by interviewing NU activists, who paid a specific concern in the agrarian sector, and by conducting a literature review of the results of NU’s ijtihad regarding agrarian reform. The result of this study indicates that agrarian reform in the RAPS policy has not fulfilled the priority fiqh principles. This article contributes to the accuracy of the concept and implementation of agrarian reform in Indonesia which is more just in accordance with the scale of priorities needed to achieve the goals of agrarian reform.Setelah bertahun-tahun ditangguhkan, reforma agraria kembali diterapkan sebagai salah satu cara untuk mewujudkan keadilan di bidang agraria. Kebijakan ini ditetapkan dalam Peraturan Presiden Nomor 86 Tahun 2018 tentang Pelaksanaan Reforma Agraria yang dibingkai dalam kebijakan Reforma Agraria dan Pergutanan Sosial (RAPS). Tetapi, kebijakan reforma agraria dalam RAPS dikritik banyak kalangan, salah satunya dari kalangan Nahdlatul Ulama (NU) yang aktif dalam perjuangan agraria. Penelitian ini akan mengkaji bagaimana dekonstruksi aktivis NU terhadap konsep reforma agraria dalam kebijakan RAPS dengan menggunakan teori fikih prioritas. Fikih prioritas merupakan salah satu teori dalam fikih kontemporer yang digagas untuk mempertimbangkan pelaksanaan amal atau kebijakan yang perlu diprioritaskan berdasarkan kaidah-kaidah syari’at. Metode penelitian yang digunakan yaitu penelitian hukum empiris dan normatif, dengan mewawancarai para aktivis NU concern di bidang agraria serta kajian literatur terhadap hasil ijtihad NU mengenai reforma agraria. Hasil penelitian ini menunjukkan bahwa reforma agraria dalam kebijakan RAPS belum memenuhi kaidah fikih prioritas. Artikel ini berkontribusi untuk mengakurasi konsep dan implementasi reforma agraria di Indonesia yang lebih adil sesuai dengan skala prioritas yang dibutuhkan untuk menggapai tujuan reforma agraria.